THE EFFECT OF THE TWO STAY TWO STRAY COOPERATIVE LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN THE BASIC PRINCIPLES OF BUILDING DESIGN AND INFORMATION MODELING (DPIB) COURSE IN GRADE X AT SMKN 1 BUKITTINGGI - Putri, Rahma Wati; Giatman, M (Jurnal Applied Science in Civil Engineering, 2023)
The focus of this study centers on the learning outcomes of Grade X DPIB students at SMKN 1 Bukittinggi influenced by the Two Stay Two Stray cooperative learning approach. Many teachers tend to prefer conventional teaching approaches that emphasize content delivery over direct interaction in basic DPIB subjects. This poses a challenge for students who are less active in the classroom learning process, as the lecture-based teaching method is not always easily understood by all students. To better achieve learning objectives, an innovative teaching approach is needed to encourage active student participation in the teaching-learning process. One proposed solution is the Two Stay Two Stray cooperative learning approach, where two students work together in discussion and two other students join them to support the learning process. This approach has the advantage of encouraging students to actively contribute to discussions, ask questions, and articulate and consolidate their understanding. To identify differences in the characteristics of the research subjects, a quasi-experimental method was employed. The research results obtained through the Mann Whitney statistical test showed an Asymp.Sig. (2-tailed) value of 0.000. This value, less than 0.05, indicates that the alternative hypothesis (Ha) can be accepted. In other words, it can be concluded that there is a significant improvement in student learning achievement in the Basic DPIB subjects in Grade X at SMKN 1 Bukittinggi when the Two Stay Two Stray cooperative learning method is implemented.